2012
DOI: 10.5539/jps.v1n2p158
|View full text |Cite
|
Sign up to set email alerts
|

Image Analysis Protocol for Detecting and Counting Viable and Inviable Pollen Grains

Abstract: Estimating total pollen number and viability is labor intensive and time consuming. Nevertheless the information is crucial for a range of plant biologists from plant breeders to evolutionary biologists. Viability is determined by dye staining and counting colored (viable) and transparent (inviable) grains under a compound microscope. Existing protocols have been standardized to speed up total pollen counts but their success in determining viability is rather limited because they do not incorporate staining te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…The high accuracy of pollen number estimation, in this study was also reported in other studies with different plant families that have different pollen size and shape (Mudd and Arathi, 2012;MacInnis and Forrest, 2017). This flexibility may be beneficial for further application on various oil palm cultivars.…”
Section: Figure 1 Various Images Resulting From Step-by-step Of Imagsupporting
confidence: 65%
See 2 more Smart Citations
“…The high accuracy of pollen number estimation, in this study was also reported in other studies with different plant families that have different pollen size and shape (Mudd and Arathi, 2012;MacInnis and Forrest, 2017). This flexibility may be beneficial for further application on various oil palm cultivars.…”
Section: Figure 1 Various Images Resulting From Step-by-step Of Imagsupporting
confidence: 65%
“…Pleura setae present in males weevils provide additional body surface which allowed the smaller debris to contaminate pollen samples (Dhileepan, 1992). Debris might form clusters with pollen which make it difficult for software to delineate individual pollen to give a correct count (Mudd and Arathi, 2012). However, for many biological studies involving counting of small biological particle, a moderate deviation (lower than 20%) is often negligible compared to noise generated by other factors (Geissman, 2013).…”
Section: Figure 1 Various Images Resulting From Step-by-step Of Imagmentioning
confidence: 99%
See 1 more Smart Citation
“…This factor has values that range from 0 (null roundness) to 1 (high roundness) [31]. For pollen grains, it is expected that cf > 0.6 [32,33]. Analysis of the dark pink cluster in our pollen sample resulted in cf = 0.55 ± 0.16 (mean ± standard deviation, mode = 0.62) for the original image, see Figs.…”
Section: Accuracy In Morphology Measurementsmentioning
confidence: 99%
“…Consequently, due to the considerable efforts required, in general, only a few hundreds of grains per replicate are counted at best. Image analysis software was used for the automation of the tests based on Alexander’s and aniline blue staining (Mudd and Arathi 2012 ; Tello et al 2018 ). Nevertheless, those stains are suited for identifying aborted or sterile grains and not for studying the state of well-developed pollen (Alexander, 1969 ; Khatun and Flowers 1995 ).…”
Section: Introductionmentioning
confidence: 99%